Hubungan Kepatuhan Minum Obat dengan Tekanan Darah pada Pasien Hipertensi di Puskesmas Mangaran - Mangundap, Lavenia Yeane; Fani, Rif'atul; Cahyaningrum, Putri (Pustaka Galeri Mandiri, 2026)
Hypertension is a chronic health problem with a high prevalence and risk of serious complications if not optimally managed, making medication adherence a crucial factor in blood pressure control. This study aims to analyze the relationship between adherence to antihypertensive medication and blood pressure status in hypertensive patients at the Mangaran Community Health Center. The study used a quantitative observational design with a correlational approach and a cross-sectional design. The study population was all hypertensive patients undergoing routine treatment, with a total sampling technique and a total of 30 respondents. Adherence data were collected using a standardized Morisky Medication Adherence Scale (MMAS-8) questionnaire, while blood pressure was measured directly according to clinical procedures. Data were analyzed univariately and bivariately using the Chi-Square Test. The results showed a significant relationship between medication adherence and blood pressure status, where higher adherence is associated with better blood pressure control. These findings provide practical implications for primary health care in strengthening education and monitoring adherence, and contribute theoretically to strengthening the concept of adherence as a major determinant of the success of hypertension therapy